Validity and Clarity of the Concepts and Terminologies of the Physical Activity Guidelines for the Brazilian Population - Benedetti, Tânia Rosane Bertoldo (2021)
We evaluated the validity and clarity of the concepts and terminologies adopted to develop the Physical Activity Guidelines for the Brazilian Population (Guidelines). The Physical Activity Domains Working Group (Domains WG) assessed the validity and clarity of the following concepts: physical activity, sedentary behavior, PA domains (free time, commuting, work or study, and household chores) and intensities (light, moderate and vigorous). The concepts were evaluated in three stages: 1- Concept proposition; 2- Expert consultation (two steps); 3- Public consultation. The concepts proposed by the Domains WG were based on international guidelines, scientific articles, official documents from the Ministry of Health, and technical-scientific academic knowledge of the Domains WG members, discussed in a series of meetings (stage 1). In the second stage (expert consultation), validity and clarity of the concepts were tested on two occasions. Seventy and forty researchers working in the other Guidelines WGs contributed to first and second steps, respectively. In both occasions, validity and clarity agreement were equal to or greater than 80% for all concepts. Suggestions provided in step 2 were adopted, and new versions of the concepts were made available for the third step, a public consultation carried out by the Ministry of Health. Fourteen suggestions related to the concepts were made and, when relevant, included in the Guidelines. According to the assessment and suggestions by experts and members of the public, the concepts and terminologies proposed by the Domains WG for the Guidelines are valid and clear.